Inhibitory effect of schizophyllan on rat glioma cells (Bangladesh Journal of Pharmacology, 2015)
The aim of this study was to examine the anticancer effects of schizophyllan (a -D-glucan) against the growth of rat CNS-1 glioma cells and preliminarily assess its effect on inducing apoptosis and blocking cell cycle. In order to evaluate its inhibitory effect, firstly MTT assay was conducted followed by annexin V/propidium iodide double staining or propidium iodide single staining, apoptosis and cell cycle using flow cytometry. All the experiments were carried in a dose- and time-dependent manner. Experimental results showed that treatment of 40 and 60 mg/L schizophyllan significantly increased the apoptotic rate and blocked the cell cycle. In addition, increase in the proportion of cells in G0/G1 phase and decrease in the proportion of S-phase cells were also observed. Overall experimental studies suggest that schizophyllan can significantly inhibit the growth of rat CNS-1 glioma cells, in vitro and induced apoptosis and blocked the cell cycle.